Model Pengembangan Keilmuan UIN Malang dan UIN Yogyakarta - Moch. Khafidz Fuad Raya (FALASIFA : Jurnal Studi Keislaman, 2017)
The integration of Islam and science is not an ordinary matter. Until now, the widespread community who said that "religion" and "science" are two entities that can not be reconciled. Both have separate territories, separate from one another, both in terms of formal object-material, research methods, truth criteria, the role played by the scientist and the status of the appointed theorist, to the institution of the organizer. From the scientific paradigm developed by UIN Maliki and UIN Likes this seems to have been the inspiration and reference for PTKI throughout Indonesia to develop Islamic universities that have a mission to integrate Islam and Science in various disciplines of science and research, it is expected later with the development of Islamic universities can answering the anxiety and anxiety of people who have been crystallized so that Muslims are shackled and stagnant in place.Â Keywords: Model Pengembangan Keilmuan UIN Malang & UIN Jogjayakarta Â